Renal allograft surveillance with allospecific T-cytotoxic memory cells - Vinayak S. Rohan; Karim M. Soliman; Ahmad Alqassieh; Duaa Alkhader; Neha Patel; Satish N. Nadig (Renal Failure, 2020)
Background Allo-antigen-specific T-cytotoxic memory cells (TcM) which express CD40 ligand (CD154) in overnight lymphocyte co-culture are strongly associated with acute cellular rejection (ACR) seen in “for cause” biopsies for renal allograft dysfunction. Specifically, when the likelihood of rejection is increased, donor-specific allospecific TcM exceed those induced by HLA-non-identical third-party cell by 1.15-fold or greater. Methods The performance of allospecific TcM was evaluated retrospectively in primary renal transplant recipients (RTR) at routine clinical visits, cross-sectionally at presentation for biopsies, and serially. Performance metrics were sensitivity, specificity, positive and negative predictive values (PPV and NPV). Results Twenty-two primary RTR, median age 45 years (range 19–72) were tested with allospecific CD154 + TcM. Samples were obtained at the mean ± SD time interval of 806 ± 239 days after kidney transplantation. Six of 22 patients experienced biopsy proven T- Cell Mediated Rejection (TCMR). A seventh showed antibody mediated rejection (ABMR). Of these seven patients six demonstrated increased likelihood of rejection with allospecific TcM (sensitivity 83%). Ten of these 15 patients with no rejection had a negative test (specificity 67%). False positive tests were seen in five patients. Six out of 11 patients with positive tests had ACR/ABMR with a PPV of 54%, while 10 out of 11 patients with negative tests were non-rejecters with a NPV of 91%. Conclusion Allospecific T-cytotoxic memory cells distinguished primary RTR with quiescent allografts from those with dysfunction. With serial surveillance measures, this test system may facilitate decisions to manage immunosuppression in RTR.